Performance Analysis of a Spatial Modulation Aided Cooperative NOMA System - Kumar M.H.; Kumar A.; Sharma S.; Kumar M.V. (My University, 2025)
In this letter, a novel communication scheme termed spatial modulation aided cooperative non-orthogonal multiple access (SM-CNOMA) is proposed for multiple-input and multiple-output (MIMO) downlink scenarios. In the SM-CNOMA system, the base station (BS) transmits information to three users across two time-slots, encompassing two near users (NUs) and a single far user (FU). Notably, NUs operate in a half-duplex mode and employ joint signal detection during the cooperative phase for decoding, and forward FU information through index modulation (IM). Bit error rate (BER) and ergodic sum-rate metrics are derived, by considering inter-user interference (IUI), of the proposed SM-CNOMA system. The impact of various system parameters, such as the number of transmit and receive antennas, is thoroughly analyzed within the SM-CNOMA framework. The presented results demonstrate that SM-CNOMA outperforms conventional CNOMA with three users and the precoded CNOMA (PCNOMA) systems. This letter contributes valuable insights into the potential benefits of SM-CNOMA in MIMO downlink communications, establishing its efficiency in mitigating interference and enhancing the overall system performance. © 2024 IEEE.